Good practices according to WHO's recommendation for normal labor and birth and women's assessment of the care received: the "birth in Brazil" national research study, 2011/2012 - Marcia Leonardi Baldisserotto; Mariza Miranda Theme Filha; Silvana Granado Nogueira da Gama (BMC, 2016)
Abstract Background The World Health Organization recommends good practices for the conduct of uncomplicated labor and birth, with the aim of improving the quality of and assessment by women of childbirth care. The aim of this study was to evaluate the association between adoption of good practices according to WHO's recommendation for normal labor and birth and assessment by women of the care received. Methods Birth in Brazil is a national hospital-based study with countrywide representation consisting of 23,894 mothers and their newborns, conducted between February 2011 and October 2012. The present study analysed a subsample of this national survey. Postpartum women classified as low risk during pregnancy who had experienced either spontaneous or induced labor were included in this study, totalling 4102 mothers. To estimate the association between assessment by women of the childbirth care received (dependent variable) and good practices according to WHO's recommendation during normal labor and birth (independent variables), a multinomial logistic regression analysis was used and crude and adjusted odds ratios calculated with their 95 % confidence intervals. Results The good practices associated with positive assessment of the care received by women during labor and birth included the partner's presence, privacy in the birthing place, time available to ask questions, clarity of information received, and empathic support from caregivers during labor and birth. Freedom of movement, free nutrition offered, choice of companions, nonpharmacological analgesia, skin-to-skin contact and breastfeeding in the childbirth room were not associated with the assessment by women of the care received. Conclusions Our findings reveal the importance to mothers of their relationship with the team of caregivers during labor and birth. Therefore, caregiver teams must be qualified within a more humanistic vision of childbirth health care.